Disparity in school children's reading skills in 11 African countries - Huafeng Zhang; Stein Terje Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
To promote SDG Goal 4 and "education for all", this study investigates children's basic reading skills in 11 low-income and lower-middle-income African countries, using standardized reading tests from the Multiple Indicator Cluster Surveys (MICS). Research specifically examining children's reading skills and disparities across socioeconomic groups in African contexts remains scarce. This study addresses a critical knowledge gap by providing comparative evidence on reading skills disparities across diverse social backgrounds, including children with disabilities. Our study provides new evidence on the "Learning Crisis in the Global South", revealing alarmingly low levels of reading skills but with considerable variation across the 11 African countries studied. Substantial reading skills differences exist between children from disadvantaged backgrounds-those with disabilities, living in rural areas, and from poorer, less educated families-and their non-disadvantaged peers. Notably, these disparities are often more pronounced in countries with higher overall reading proficiency. Moreover, there are persistent gaps between children with and without disabilities across the countries and socioeconomic groups in this study. Encouragingly, children with disabilities benefit from improved socioeconomic conditions just as much as non-disabled children. These findings underscore the diverse challenges faced by children from different disadvantaged backgrounds in varying contexts.
hdl:11250/3158906
Keywords: I24; 330; Africa; Children with disabilities (CWD); Educational inequality; Poverty; Readingskills; Socioeconomic background; Urban-rural disparity